Does problem-based learning education improve knowledge, attitude, and perception toward patient safety among nursing students? A randomized controlled trial - Hossein Jamshidi; Masumeh Hemmati Maslakpak; Naser Parizad (BMC, 2021)
Abstract Background Patient safety is a top priority for any health care system. Most universities are looking for teaching methods through which they would be able to enhance students' clinical decision-making capabilities and their self-centered learning to ensure safe and quality nursing care. Therefore, this study aimed to determine the effect of patient safety education through problem-based learning (PBL) on nursing students' knowledge, attitude, and perceptions toward patient safety. Methods This randomized, controlled trial was conducted from September 2019 to January 2020. A total of 78 fourth-year nursing students participated in this study. The participants were randomly assigned to either the intervention group or the control group. In the intervention group, the educational materials were presented to the students using the PBL method during eight sessions of 45-60 min. In each control group, nursing students received eight education sessions through lectures and discussing the same educational content. Data were gathered 1 month after the intervention using demographic information and knowledge, attitudes, and perception questionnaires. Data were analyzed in SPSS ver. 22.0 using descriptive (mean and standard deviation) and inferential (chi-square test, independent t-test, paired t-test, and analysis of covariance (ANCOVA)) statistics. Results The results indicated that the difference in the mean scores of knowledge, attitudes, and perceptions of the nursing students about patient safety was statistically significant between the two groups after the PBL education (p = 0.001). The mean scores of students' knowledge, attitude, and perceptions of patient safety increased significantly in the intervention group. Conclusions Implementing patient safety education through PBL positively affects knowledge, attitudes, and perceptions of patient safety among nursing students. Thus, the research team recommended the PBL method to be used by nursing professors to improve nursing students' clinical skills and cognitive abilities to ensure safe patient care. Trial registration IRCT20190925044881N1 ; October 17, 2019.